Overview of the Quality of Life of Breast Cancer Patients Undergoing Chemotherapy During the COVID-19 Pandemic - Dewa Gde Sudiasta; Ni Luh Gede Puspita Yanti; Ni Ketut Citrawati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Chemotherapy as an option for breast cancer treatment. The Covid-19 pandemic has had a serious impact on health services, one of which is chemotherapy services. The delay in chemotherapy services due to the increasing number of COVID-19 cases indirectly has an impact on the quality of life of breast cancer patients undergoing chemotherapy. The purpose of this study was to describe the quality of life of breast cancer patients undergoing chemotherapy during the COVID-19 pandemic. The design of this study used a quantitative descriptive with a cross sectional design. The study was conducted in the Chemotherapy Room Sanjiwani RSUP Sanglah with a sample size of 50 respondents with a sampling technique using purposive sampling. The results of this study indicate that the majority of breast cancer patients have quality of life in the moderate category as many as 47 respondents (96%) with an average quality of life score of 649.45 in the moderate category. Moderate quality of life in cancer patients is due to chemotherapy which improves the patient’s healing process so that there is an increase in quality of life. It is hoped that health workers will receive IEC and motivation for breast cancer patients undergoing chemotherapy during the COVID-19 pandemic as an effort to improve the patient's quality of life